To Maintain or Cease Non–Vitamin K Antagonist Oral Anticoagulants Prior to Minimal Bleeding Risk Procedures: A Review of Evidence and Recommendations - Brennan, Yvonne; Favaloro, Emmanuel J.; Curnow, Jennifer (Seminars in Thrombosis and Hemostasis, 2019)
For procedures associated with minimal bleeding risk, there are data and experience to support the practice of continuing vitamin K antagonists rather than interrupting therapy, to prevent exposing patients to the undue risk of developing thromboembolism during anticoagulation cessation. Despite the increasing use of non–vitamin K oral anticoagulants (NOACs), there is little evidence to guide the management of these drugs around minimal bleeding risk procedures. This review examines and discusses the major society guidelines and recommendations addressing the management of NOACs around minimal bleeding risk procedures. Additionally, it summarizes the existing evidence, and highlights the gaps in knowledge where evidence is not yet available. Finally, recommendations are made to assist the proceduralist deal with this area of limited evidence.
Keywords: Non–vitamin K oral anticoagulants; direct oral anticoagulants; anticoagulation; surgery; minimal bleeding risk; dental procedure; dermatologic surgery